Reformasi terminologi kurikulum dan pengaruhnya terhadap kesiapan mengajar guru - Septi Yunita; Cepi Riyana; Dadi Mulyadi (Curricula: Journal of Curriculum Development, 2026)
The change in terms such as Kompetensi Dasar (KD) to Capaian Pembelajaran (CP), and Silabus to Alur Tujuan Pembelajaran (ATP) is not merely linguistic, but also carries conceptual consequences that require teachers to reinterpret the meaning and direction of the policy. The lack of comprehensive explanations, socialization, and implementation support leads to a mismatch between teachers' understanding and the curriculum's demands, thereby affecting their readiness to design and implement learning. Based on these conditions, this study aims to analyze how changes in curriculum terminology affect teachers' readiness, both in conceptual understanding and in teaching practice. This study uses a literature study approach with descriptive analysis of literature discussing curriculum changes and their impact on teacher readiness. The results of the study indicate that changes in terminology affect teachers' pedagogical, psychological, and professional aspects. Therefore, ongoing mentoring strategies, effective communication between stakeholders, and teacher involvement in professional learning communities are needed. These findings confirm that the success of curriculum implementation is largely determined by teachers' readiness to understand and apply the new terminology fully.